In Vitro Assessment of Selected Medicinal Plants Used by the Bapedi Community in South Africa for Treatment of Bacterial Infections - Refilwe Given Kudumela MSc; Peter Masoko PhD (SAGE Publishing, 2018)
There is very little scientific information on indigenous plants used for medicinal purposes. Therefore, the aim of the study was to evaluate the antibacterial and antioxidant activities of the leaves of Commelina africana , Elephantorrhiza elephantina , Dombeya rotundifolia , and the whole plant excluding the roots of Schkuhria pinnata indigenous medicinal plants from the Limpopo Province, which may be used for the treatment in humans infected with bacterial pathogens. The screening of different phytoconstituents using standard methods revealed the presence of terpenoids, flavonoids, tannins, and saponins. The total phenolic, tannin, and flavonoid content were estimated using spectrophotometric methods. D rotundifolia had the highest amounts of phenol (259.00 ± 2.65 mg of gallic acid equivalent [GAE]/g), tannin (330.33 ± 15.63 mg of GAE/g), and flavonoid (19.90 ± 0.75 mg of quercetin equivalent [QE]/g) content, while S pinnata had the least. All the plants had antibacterial activity against Escherichia coli and Pseudomonas aeruginosa with the bioautography method. The microbroth dilution assay revealed antibacterial activity with minimum inhibitory concentration values raining from 0.02 to 2.50 mg/mL. D rotundifolia had the highest antioxidant activity in both the free radical scavenging and ferric reducing power methods. S pinnata and C africana extracts had high antibacterial activity, while D rotundifolia had high antioxidant activity, which made them potential plants for isolation of bioactive compounds and possible application in the pharmaceutical industry.